Cerebrovascular Steal Phenomenon and Electroconvulsive Therapy: A Case Report and Review of the Literature. Issue 2 (June 2018) - Hategan, Ana; Hirsch, Calvin H.
Abstract : Abstract: Electroconvulsive therapy (ECT) is a safe and effective treatment for major depressive disorder, but cerebrovascular and cardiovascular complications, although rare, remain the most concerning. This is particularly notable in those with preexisting cerebrovascular disease, which impacts dynamic cerebral autoregulation. In these patients, the increased blood flow to the seizing portions of the brain induced by ECT potentially can reduce cerebral blood flow to ischemic areas, possibly causing adverse neurological events. The authors describe a patient with chronic cerebral ischemic disease, chronic anemia, and major depressive disorder undergoing ECT to achieve remission. The patient developed recurrent focal neurological deficits after each ECT procedure, with neurological recovery within 48 hours post-ECT. Clinical guidelines may need to be updated for the management of ECT patients with cerebrovascular disease who may be at an increased risk of intraictal and possibly postictal regional ischemia, especially in areas already compromised by a prior stroke and/or by reduced cerebral oxygenation caused by symptomatic anemia at risk of ischemia. Research is needed to assess changes in regional cerebral blood flow during and after ECT in patients with cerebrovascular disease, including small-vessel cerebral ischemia, and to evaluate these changes in relation to the location, intensity, and duration of induced seizure.